Adolescent Self Regulation to Prevent Hypertension and Affecting Factors - Dwi Ananto Wibrata; Siti Nur Kholifah; Moh. Bahrudin; Nikmatul Fadilah (Health Notions, 2022)
Introduction: Unhealthy behavior in adolescents requires self-regulation to change it. The purposed of behavior change was to prevent hypertension. The purpose of the studied was to determine adolescent self-regulation in preventing hypertension and the factors that influence it. Methods: This type of research is analytic observational, cross sectional design. The population of this research is the second grade junior high school students in Surabaya. The sample size is 210 people. Sampling with probability sampling type multistage sampling. The variables studied were self-regulation and external driving factors. Data analysis using SEM. Results: The regulation of self-care in adolescents in physical activities and sports is mostly sufficient, the regulation of eating is sufficient, stress management is mostly sufficient, efforts to avoid smoking are mostly sufficient and monitoring of ideal body weight is mostly lacking. Analysis using the t test showed that there was a significant influence between the driving factors for self-regulation with p = 0.022. Discussion: External driving factors are important for adolescents to regulate their behavior in preventing hypertension. Family can become a role model for adolescents. Cooperation with health workers to provide education in schools is needed to increase adolescent knowledge. Keywords: self regulation; adolescent; prevent; hypertension